Sosialisasi dan Pendampingan Pendaftaran Kartu Indonesia Pintar Kuliah (KIP-K) Bagi Siswa-Siswi Tidak Mampu di Kepulauan Sula Maluku Utara - Aji Saputra; Mirda Prisma Wijayanto; Andy Hermawan; Ismi Musdalifah Darsan; Roni Kurniawan; Hutri Handayani Isra; Krishna Aji; Zandy Pratama Zain; Sheila Kusumaningrum; Rusandry Rusandry; Sartika Putri Sailuddin; Firmansyah Firmansyah; Agatha Christy Situru; Syahrial Maulana; Iwan Abdy (Lembaga Pengembangan Kinerja Dosen, 2024)
Kartu Indonesia Pintar Kuliah (KIP-K) is a scholarship given by the government to high school graduates and equivalent who excel but have economic limitations to continue their studies at university level, both at state and private universities. The Indonesian government has issued the KIP-K since 2020 as a form of educational assistance. In North Maluku Province, especially on Sula Island, there is still minimal information regarding KIP-K. This service activity aims to share information regarding the benefits of higher education and how to obtain a KIP-K scholarship for students who have financial limitations. This community service is carried out at SMAN 1 Kepulauan Sula, MAN 1 Kepulauan Sula, SMAN 7 Kepulauan Sula, SMAN 9 Kepulauan Sula and SMAN 11 Kepulauan Sula. This activity was carried out in two stages, namely socialization and mentoring. The implementation of this activity went well, smoothly and was full of enthusiasm from the participants, especially students who wanted to continue their studies at university level. The final result of this socialization and mentoring is that the participants have succeeded in creating their own accounts, filling in data and registering for KIP-K.